Numerical deformability analysis of composite panels used for construction of ventilation and air-conditioning ducts - Kegler, Krzysztof; Cichowicz, Robert; Kamiński, Marcin (Instal, 2024)
This article presents the numerical simulations using ANSYS software to analyze deformation of the ventilation and air conditioning ducts made of composite materials. The application of the Finite Element Method for nonlinear static analysis of deformation of such systems with 3D brick finite elements has been discussed. The proposed numerical simulation has been calibrated with the previous laboratory experiments, in which multilayer composite plates used in ventilation and air-conditioning systems have been examined. The efficient numerical model, that has been established thanks to this comparison, may serve in the future to optimize the existing engineering solutions. It could also be efficient in strengthening of the existing ducts with the composite strips. This will enable a remarkable increase of the ducts strength and reliability with preservation of the most important pros of these ducts.
Keywords: Finite Element Method; laminar composite